Impact of caregiver interventions on caregiver burden in adult traumatic brain injury: a systematic review and meta-analysis - Ting, Chung Yan; Ahmed, Zubair (Frontiers in Public Health, 2025)
BackgroundTraumatic brain injury (TBI) has been known to cause physical and psychological dysfunction among patients. Most family members face numerous physical and psychological difficulties in caregiving, yet effective interventions remain limited. This study aims to (a) identify the effects of caregiver interventions on caregiver burden for traumatic brain injury patients, (b) evaluate the effects of these programs on caregivers' psychological distress.MethodsA systematic search was conducted in Pubmed, Medline and PsycINFO to search for randomized control trials (RCTs) that report the effects of caregiver interventions on care partners of TBI patients above the age of 18. The primary outcome was caregiver burden, which was measured mainly using the Zarit Burden Interview (ZBI). The secondary outcome was psychological distress, with the Brief Symptom Inventory-18 (BSI-18) as the main assessment used. The RoB-2 tool was used to assess the risk of bias.ResultsThirteen RCTs were identified after screening. Meta-analysis of the primary outcome (ZBI) showed significant improvements (p < 0.05) favoring intervention despite high heterogeneity in the 5 studies. Meta-analysis of the secondary outcome (BSI-18) indicated smaller but significant improvement (p = 0.02) with low heterogeneity in 3 studies.ConclusionResults suggest that caregiver interventions are effective in improving caregiver burden and psychological distress in the future. However, due to high risk of bias in studies, the conclusion should be interpreted with caution before clinical application. Higher quality research should be conducted to ensure the effectiveness of caregiver programs.